DEVELOPMENT OF FLIPBOOK-BASED LEARNING MEDIA IN THE SUBJECT OF TRANSACTION ADMINISTRATION - Junevta, Sarah Melissa; Faslah, Roni; Fidhyallah, Nadya Fadillah (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
The development of flipbook-based learning e-modules to improve learning outcomes is motivated by the lack of variation in the teaching materials used, too many files that must be saved, students tend to have difficulty understanding learning materials, especially Transaction Administration materials. This study is to determine the feasibility and practicality of developing interactive flipbooks in transaction administration subjects. This study was conducted using the Research and Development method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model at SMK Tamansiswa 1 Jakarta in class XI as many as 59 students. The data analysis techniques used were media expert tests, material expert tests and material and media expert tests. The results showed that the flipbook-based transaction administration learning e-module after being validated by material experts with a total score percentage of 80% was included in the good category. The assessment carried out by media expert validation with a score percentage of 70% on the Technical Format aspect was included in the good category and a score percentage of 90% on the Visual Design aspect was included in the very good category. The assessment carried out by media and material expert validation carried out by educators with a score percentage of 100% is included in the very good category.